5-Year Clinical Outcomes of Successful Recanalisation for Coronary Chronic Total Occlusions in Patients With or Without Type 2 Diabetes Mellitus - Wang, Peizhi; Yuan, Deshan; Jia, Sida; Zhu, Pei; Zhang, Ce; Liu, Yue; Li, Tianyu; Jiang, Lin; Song, Ying; Xu, Jingjing; Tang, Xiaofang; Zhao, Xueyan; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Despite substantial improvement in chronic total occlusions (CTO) revascularization technique, the long-term clinical outcomes in diabetic patients with revascularized CTO remain controversial. Our study aimed to investigate the five-year cardiovascular survival for patients with or without type 2 diabetes mellitus (DM) who underwent successful percutaneous coronary intervention (PCI) for CTO. Methods: Data of the current analysis derived from a large single-center, prospective and observational cohort study, including 10,724 patients who underwent PCI in 2013 at Fuwai Hospital. Baseline, angiographic and follow-up data were collected. The primary endpoint was major adverse cardiac and cerebrovascular events (MACCE), which consisted of death, recurrent myocardial infarction (MI), stroke and target vessel revascularization (TVR). The secondary endpoint was all-cause mortality. Cox regression analysis and propensity-score matching was performed to balance the baseline confounders. Results: A total of 719 consecutive patients with ≥ 1 successful CTO-PCI were stratified into diabetic (n=316, 43.9%) and non-diabetic (n=403, 56.1%) group. During a median follow-up of 5 years, the risk of MACCE (adjusted hazard ratio [HR] 1.47, 95% confidence interval [CI] 1.08-2.00, P = 0.013) was significantly higher in the diabetic group than in the non-diabetic group, whereas the adjusted risk of all-cause mortality (HR 2.37, 95% CI 0.94-5.98, P = 0.068) was similar. In the propensity score matched population, there were no significant differences in the risk of MACCE (HR 1.27, 95% CI 0.92-1.75, P = 0.155) and all-cause mortality (HR 2.56, 95% CI 0.91-7.24, P = 0.076) between groups. Subgroup analysis and stratification analysis revealed consistent effects on five-year MACCE across various subgroups. Conclusions: In patients who received successful CTO-PCI, non-diabetic patients were related to better long-term survival benefit in terms of MACCE. The risk of five-year MACCE appeared to be similar in less-controlled and controlled diabetic patients after successful recanalization of CTO. Further randomized studies are warranted to confirm these findings.